The diversity and ethnobotanical study of medicinal plants in the southern slope of Mount Merapi, Yogyakarta, Indonesia - MAIZER SAID NAHDI; ARDYAN PRAMUDYA KURNIAWAN (Society for Indonesian Biodiversity, 2019)
Abstract. Nahdi MS, Kurniawan AP. 2019. The diversity and ethnobotanical study of medicinal plants in the southern slope of Mount Merapi, Yogyakarta, Indonesia. Biodiversitas 20: 2279-2287. Medicinal plants have been widely used by local communities in Indonesia due to its effectiveness as medicine and its low cost. In addition, the scientific and technological development of medicinal plants has been developed rapidly. This research aims to conduct inventory of medicinal plants recorded in the ecosystem of the southern slope of Mount Merapi, Yogyakarta and to reveal the local knowledge on their uses and traditional healing method applied. We used a combination of qualitative and quantitative methods. The data of local knowledge on medicinal plants and traditional medical practices when using them were collected through in-depth and semi-structured interview with local informants selected through purposive and snowball sampling. The results showed that the abundance of medicinal plant species at the study area was very high during the rainy season, while during the dry season, some of the plant species were found in the yard and open land. A total of 82 species from 40 families were identified as medicinal plants and used by the community through various processing and for various medical treatments. The information was inherited from previous generations through counseling and training. The most favorable way to use medicinal plants was by consuming the leaf directly. Among all identified medicinal plants, betel leaves (Piper betle L) had the highest importance value (43.6%), followed by turmeric (Curcuma longa L) (38.5%), and soursop (Annona muricata L) (33.3%). Kelor (Moringa pterygosperma, Gaertn) had the most significant usage value (0,6), followed by lemongrass (Cymbopogon citratus (DC) Stapf) and ginger (Curcuma xanthorrhiza Roxb) with the same value (0.3). The medicinal plants had also co-benefits including to encourage communication as well as to building relationship among community members.